Detraining: loss of training-induced physiological and performance adaptations. Part II: long term insufficient training stimulus - Mujika, I.; Padilla, S. (Sports Medicine, 2000)
This part II discusses detraining following an insufficient training stimulus period longer than 4 weeks, as well as several strategies that may be useful to avoid its negative impact. The maximal oxygen uptake (VO2max) of athletes declines markedly but remains above control values during long term detraining, whereas recently acquired VO2max gains are completely lost. This is partly due to reduced blood volume, cardiac dimensions and ventilatory efficiency, resulting in lower stroke volume and cardiac output, despite increased heart rates. Endurance performance is accordingly impaired. Resting muscle glycogen levels return to baseline, carbohydrate utilisation increases and the lactate threshold is lowered, although it remains above untrained values in the highly trained. At the muscle level, capillarisation, arterial-venous oxygen difference and oxidative enzyme activities decline in athletes and are completely reversed in recently trained individuals, contributing significantly to the long term loss in VO2max. Oxidative fibre proportion is decreased in endurance athletes, whereas it increases in strength athletes, whose fibre areas are significantly reduced. Force production declines slowly, and usually remains above control values for very long periods. All these negative effects can be avoided or limited by reduced training strategies, as long as training intensity is maintained and frequency reduced only moderately. On the other hand, training volume can be markedly reduced. Cross-training may also be effective in maintaining training-induced adaptations. Athletes should use similar-mode exercise, but moderately trained individuals could also benefit from dissimilar-mode cross-training. Finally, the existence of a cross-transfer effect between ipsilateral and contralateral limbs should be considered in order to limit detraining during periods of unilateral immobilisation.